CECAM workshop on intrinsically disordered proteins: Connecting computation, physics, and biology ETH Zürich September 2nd to 5th, 2013 - Rösner, Heike (Intrinsically Disord Proteins, 2014)
With the increasing need to integrate different areas of science in the study of intrinsically disordered proteins we arranged a meeting entitled “Intrinsically Disordered Proteins: Connecting Computation, Physics and Biology” in Zürich in September 2013. The aim of the meeting was to bring together scientists from a range of disciplines to provide a snapshot of the field, as well as to promote future interdisciplinary studies that link the fundamental physical and chemical properties of intrinsically disordered proteins with their biological function. A range of important topics were covered at the meeting including studies linking structural studies of intrinsically disordered proteins with their function, the effect of post-translational modifications, studies of folding-upon-binding, as well as presentation of a number of systems in which intrinsically disordered proteins play a central role in important biological processes. A recurring theme was how computation, including various forms of molecular simulations, can be integrated with experimental and theoretical studies to help understand the complex properties of intrinsically disordered proteins. With this Meeting Report we hope to give a brief overview of the inspiration obtained from presentations, discussions and conversations held at the workshop and point out possible future directions within the field of intrinsically disordered proteins.